2022
DOI: 10.1038/s41386-022-01505-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel non-stimulants rescue hyperactive phenotype in an adgrl3.1 mutant zebrafish model of ADHD

Abstract: ADHD is a highly prevalent neurodevelopmental disorder. The first-line therapeutic for ADHD, methylphenidate, can cause serious side effects including weight loss, insomnia, and hypertension. Therefore, the development of non-stimulant-based therapeutics has been prioritized. However, many of these also cause other effects, most notably somnolence. Here, we have used a uniquely powerful genetic model and unbiased drug screen to identify novel ADHD non-stimulant therapeutics. We first found that adgrl3.1 null (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…We also validated using an established transgenic line, adgrl3.1 -/-, which was employed because previous studies had shown robust hyperactivity compared to WT (Sveinsdóttir et al, 2023). We aimed to demonstrate the ability of our assay to distinctly establish specific drug effects by demonstrating the common adverse effect, sedation, in the WT ATO exposed larvae (Bastiaens, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We also validated using an established transgenic line, adgrl3.1 -/-, which was employed because previous studies had shown robust hyperactivity compared to WT (Sveinsdóttir et al, 2023). We aimed to demonstrate the ability of our assay to distinctly establish specific drug effects by demonstrating the common adverse effect, sedation, in the WT ATO exposed larvae (Bastiaens, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The fish used in this study were homozygous adgrl3.1 mutant zebrafish ( adgrl3.1-/- ) created by CRISPR-Cas9 genome engineering, as previously described 29 , and age-matched adgrl3.1 +/+ controls. Adult fish were housed in an aquarium facility at the University of Portsmouth (UK), and kept on a 14:10 light: dark cycle (28°C, pH~8).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Adgrl3 -/- rats and mice, and both adgrl3.1 antisense morpholino oligonucleotide (MO) knock-down and adgrl3.1 -/- knock-out zebrafish larvae display persistent hyperactivity 24, 27 which is rescued by both stimulant and non-stimulant ADHD treatments (e.g. the dopamine (DAT) reuptake inhibitor methylphenidate 28 and the noradrenaline (NET) reuptake inhibitor atomoxetine 29 28 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of adglr3.1 −/− sh The sh used in this study were homozygous adgrl3.1 mutant zebra sh (adgrl3.1-/-) created by CRISPR-Cas9 genome engineering, as previously described 29 , and age-matched adgrl3.1+/+ controls. Adult sh were housed in an aquarium facility at the University of Portsmouth (UK), and kept on a 14:10 light: dark cycle (28°C, pH ~ 8).…”
Section: Methodsmentioning
confidence: 99%